Un estudio de liderazgo administrativo = An administrative leadership study. - Aldape, T. (Universidad Autónoma de Nuevo León, 2007)
Abstract. This article presents an study results aiming to explore higher level (managers) and lowest level (operators) of an organization dedicated to produce lime, about required leadership characteristics and competences during a period of transition and change of the organization’s design.